A lysosomal chloride ion-selective fluorescent probe for biological applications. Issue 1 (27th November 2018) - Park, Sang-Hyun; Hyun, Ji Young; Shin, Injae
Abstract : Changes in lysosomal Cl − concentrations induced by various substances are determined using a lysosomal chloride-selective fluorescent probe. Abstract : Lysosomal pHs are maintained at low values by the cooperative action of a proton pump and a chloride channel to maintain electroneutrality. Owing to the biological significance of lysosomal chloride ions, measurements of their levels are of great importance to understand lysosome-associated biological events. However, appropriate probes to selectively detect Cl − ions within acidic lysosomes have not been developed to date. In this study, we prepared MQAE-MP, a lysosomal Cl − -selective fluorescent probe, and applied it to gain information about biological processes associated with lysosomes. The fluorescence of MQAE-MP is pH-insensitive over physiological pH ranges and is quenched by Cl − with a Stern–Volmer constant of 204 M −1 . Because MQAE-MP detects lysosomal Cl − selectively, it was employed to assess the effects of eleven substances on lysosomal Cl − concentrations. The results show that lysosomal Cl − concentrations decrease in cells treated with substances that inhibit proteins responsible for lysosomal membrane stabilization, induce lysosomal membrane permeabilization, and transport lysosomal Cl − to the cytosol. In addition, we investigated the effect of lysosomal chloride ions on the fusion of autophagosomes with lysosomes to generate autolysosomes during autophagy inhibition promoted by substances. It was found that changes in lysosomal Cl − concentrations did not affect the fusion of autophagosomes with lysosomes but an increase in the cytosolic Ca 2+ concentration blocked the fusion process. We demonstrate from the current study that MQAE-MP has great potential as a lysosomal Cl − -selective fluorescent probe for studies of biological events associated with lysosomes.